(4a-3)(a+4)=0

Simple and best practice solution for (4a-3)(a+4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4a-3)(a+4)=0 equation:


Simplifying
(4a + -3)(a + 4) = 0

Reorder the terms:
(-3 + 4a)(a + 4) = 0

Reorder the terms:
(-3 + 4a)(4 + a) = 0

Multiply (-3 + 4a) * (4 + a)
(-3(4 + a) + 4a * (4 + a)) = 0
((4 * -3 + a * -3) + 4a * (4 + a)) = 0
((-12 + -3a) + 4a * (4 + a)) = 0
(-12 + -3a + (4 * 4a + a * 4a)) = 0
(-12 + -3a + (16a + 4a2)) = 0

Combine like terms: -3a + 16a = 13a
(-12 + 13a + 4a2) = 0

Solving
-12 + 13a + 4a2 = 0

Solving for variable 'a'.

Factor a trinomial.
(-4 + -1a)(3 + -4a) = 0

Subproblem 1

Set the factor '(-4 + -1a)' equal to zero and attempt to solve: Simplifying -4 + -1a = 0 Solving -4 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1a = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1a = 0 + 4 -1a = 0 + 4 Combine like terms: 0 + 4 = 4 -1a = 4 Divide each side by '-1'. a = -4 Simplifying a = -4

Subproblem 2

Set the factor '(3 + -4a)' equal to zero and attempt to solve: Simplifying 3 + -4a = 0 Solving 3 + -4a = 0 Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -4a = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -4a = 0 + -3 -4a = 0 + -3 Combine like terms: 0 + -3 = -3 -4a = -3 Divide each side by '-4'. a = 0.75 Simplifying a = 0.75

Solution

a = {-4, 0.75}

See similar equations:

| 1x-2y=-4 | | a-18=54 | | g+4.5=12 | | 2/3(8a-15)=7/9 | | 18-2(7-4)= | | -5=4+k | | (-2x+7)-(x+11)= | | 3x-7x+37=2x+31 | | 4x-5+2x+10+4x-5=180 | | (4+9)(-11)=121 | | -5=4k | | -3(c+2)+c=14 | | 1000=d-100 | | -5(1+7n)-n=-113 | | -8t+2t= | | 3/5*5/12= | | 9c+6=10c | | 2m+7-7=10+2m+18 | | -10=c-14 | | 11r-7s= | | 15(7c-5)=8c-3 | | 57=50x | | 38-3x=4x-18 | | Z-9=54.9 | | h=t^2+5t+6 | | 3x+8-12=2(2x-3)+x | | 1/2(3x2) | | 2/3x9/16 | | 7-5m=18+2m | | (5x-10)=37 | | 5(4+2x)+(-8x+-12)=68 | | (x+24)=(2x-1) |

Equations solver categories